2019
DOI: 10.1186/s43042-019-0040-3
|View full text |Cite
|
Sign up to set email alerts
|

Omphalocele: a review of common genetic etiologies

Abstract: Omphalocele is one of the most common congenital defects in the anterior abdominal wall. The malformation is associated with various pathologies especially with chromosomal disorders. The developmental defect is observed in Congolese hospitals, but risk factors are not well precised on the published case reports, which are more often focused on management. We aim in this paper to make a review on the condition, insisting on the risk factors of omphaloceles mainly of those of genetic origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…28 An omphalocele is usually associated with other major anomalies and aneuploidy and thus mandates a complete foetal evaluation including karyotype. 29 Possibility of a lethal lysosomal storage disorder as a cause of non-immune hydrops fetalis (NIHF) as seen in foetus 8 can be kept and a cordocentesis for enzyme analysis can be offered for such cases. 30…”
Section: Resultsmentioning
confidence: 99%
“…28 An omphalocele is usually associated with other major anomalies and aneuploidy and thus mandates a complete foetal evaluation including karyotype. 29 Possibility of a lethal lysosomal storage disorder as a cause of non-immune hydrops fetalis (NIHF) as seen in foetus 8 can be kept and a cordocentesis for enzyme analysis can be offered for such cases. 30…”
Section: Resultsmentioning
confidence: 99%
“…Omphalocele is a midline anterior abdominal wall defect in which there is herniation of the abdominal viscera covered by a thin membrane [19]. Other studies also reported omphalocele as the most common congenital abdominal wall defect [20,21]. The absence of facilities required for the assessment of chromosomal and other associated anomalies is the challenge encountered in the management of omphalocele.…”
Section: Discussionmentioning
confidence: 99%
“…At birth, it is approximately 2:10,000 3–7 . Omphalocele seems to be due to a primary failure of the lateral ventral folds, which form the primitive umbilical ring and an incomplete migration and differentiation of the mesodermal somites 3,8–10 . Since midgut herniation remains a physiological finding up to the 12th week of gestation, this is a differential diagnosis and isolated omphalocele cannot be reliably diagnosed on prenatal ultrasound until after 12 weeks 5,11–17 .…”
Section: Introductionmentioning
confidence: 99%